2008
DOI: 10.1093/cvr/cvn030
|View full text |Cite
|
Sign up to set email alerts
|

Free fatty acids act as endogenous ionophores, resulting in Na+ and Ca2+ influx and myocyte apoptosis

Abstract: AA and FFAs, which accumulate in the myocardium during post-I/R, may therefore act as naturally occurring endogenous ionophores and contribute to the myocyte death seen during post-I/R.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 38 publications
4
22
0
Order By: Relevance
“…12-HETE, 20-HETE, and 8-HDoHE), but not 14,15-EET, 9-oxoODE, or PGE 2 , sensitize mitochondria to the calcium-induced loss of membrane potential. These findings are supported by previous studies that showed arachidonic acid-and 12-HETE-facilitated Ca 2ϩ overload resulting in abnormal oxidative stress and mitochondrial dysfunction (44,49). Therefore, the results of this study suggest that iPLA 2 ␥ facilitates production of oxidized lipid metabolites by providing PUFAs and/or polyunsaturated fatty acyl lysolipids, which can be further hydrolyzed to non-esterified PUFAs by lysophospholipases and subsequent oxidation by downstream oxygenases.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…12-HETE, 20-HETE, and 8-HDoHE), but not 14,15-EET, 9-oxoODE, or PGE 2 , sensitize mitochondria to the calcium-induced loss of membrane potential. These findings are supported by previous studies that showed arachidonic acid-and 12-HETE-facilitated Ca 2ϩ overload resulting in abnormal oxidative stress and mitochondrial dysfunction (44,49). Therefore, the results of this study suggest that iPLA 2 ␥ facilitates production of oxidized lipid metabolites by providing PUFAs and/or polyunsaturated fatty acyl lysolipids, which can be further hydrolyzed to non-esterified PUFAs by lysophospholipases and subsequent oxidation by downstream oxygenases.…”
Section: Discussionsupporting
confidence: 90%
“…The rapid lateral diffusion of the released saturated fatty acid in the plane of the inner membrane allows it to directly interact with the mPTP without sequestration by cytosolic fatty acid-binding proteins. The regulatory effects of palmitate on the mPTP are further aggravated by its ability to induce ER Ca 2ϩ depletion and reactive oxygen species generation (47,48) and by acting as an endogenous ionophore (49). Supporting these mechanisms, deletion of mitochondrial membrane-associated iPLA 2 ␥ led to the remarkable and robust salvage of damaged regions of myocardium after I/R, which emphasizes a prominent role of car- In addition to iPLA 2 ␥-mediated release of saturated fatty acids from phospholipid pools, we previously reported marked iPLA 2 ␥-dependent production of cardiac eicosanoids in the myocardium by utilizing cardiac myocyte-specific overexpression of iPLA 2 ␥ and global iPLA 2 ␥ knock-out mice (34).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that different FFAs, including palmitic acid (16:0), stearic acid (18:0), and oleic acid (18:1), change. Fang et al ( 28 ) showed that arachidonic acid (20:0), palmitic acid (C16:0), oleic acid (C18:1), and linoleic acid (18:2) also play important roles during ischemic reperfusion, which impacts ion channels. Both palmitic and oleic acid induce intracellular Ca 2+ and Na + production in a dose-dependent manner by opening permeability transition pores.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has indicated that AA is involved in cell apoptosis via the induction of Ca 2+ overload, increase in mitochondrial membrane permeability, release of cytochrome c and activation of caspase-3, which eventually leads to cell apoptosis and death [16,17] . Figure 3B and C).…”
Section: Gdcl 3 Inhibited A/r-induced Cardiomyocyte Apoptosis In Vitromentioning
confidence: 99%
“…Previous studies have demonstrated that mitochondrial-related pathways and death receptor-mediated pathways are involved in I/Rinduced cardiomyocyte apoptosis [13][14][15] . Therefore, the exploration of the mechanisms of myocardial I/R-induced apoptosis and the identification of the potential target(s) to prevent or reverse cell apoptosis are important for the prevention and Several studies have suggested that a large concentration of arachidonic acid (AA) is released from cell membrane phospholipids under pathological conditions, such as stress, ischemia, hypoxia, and I/R, thus leading to multiple deleterious consequences, including abnormal excitation-contraction coupling due to alterations in ion channel kinetics, bioenergetic inefficiency, apoptosis, and accelerated necrosis, which collectively promote the development of heart dysfunction, heart failure, and sudden death [16,17] . Accumulating evidence has indicated that AA-induced cell apoptosis partially occurs through mitochondria-mediated pathways via an increase in mitochondrial membrane permeability, the release of cytochrome c, and caspase-3 activation, which induces apoptosis and cell death [17] .…”
Section: Introductionmentioning
confidence: 99%